2020
DOI: 10.3390/ijerph17165629
|View full text |Cite
|
Sign up to set email alerts
|

Association between Social Trust and Metabolic Syndrome in a Previously Healthy Population—A Longitudinal Cohort Study in South Korea

Abstract: Background: Social trust, assessed by the trustworthiness of one another in a community, is known to have beneficial effects on health outcomes. However, the impact of social trust on metabolic syndrome (MetS) is unclear. Methods: The study subjects were extracted from the Korean National Health Insurance Service, and social trust was obtained from the Korean Community Health Survey (KCHS). Previously healthy participants were followed up from 1 January 2010 to 31 December 2011, and again from 1 January 2012 t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 29 publications
1
5
1
Order By: Relevance
“…Contrary to previous studies [ 20 , 23 , 54 ], however, the level of social support in this study did not affect the risk level of MetS. In previous studies, it was found that the sense of belonging as a community and a high level of social support promote physical and psychological health because they provides a sense of emotional stability in relationships among residents [ 23 ].…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Contrary to previous studies [ 20 , 23 , 54 ], however, the level of social support in this study did not affect the risk level of MetS. In previous studies, it was found that the sense of belonging as a community and a high level of social support promote physical and psychological health because they provides a sense of emotional stability in relationships among residents [ 23 ].…”
Section: Discussioncontrasting
confidence: 99%
“…In previous studies, it was found that the sense of belonging as a community and a high level of social support promote physical and psychological health because they provides a sense of emotional stability in relationships among residents [ 23 ]. The finding that social support within the community affects the improvement of health outcomes (e.g., individual health level, well-being, and quality of life) are consistently supported by various studies [ 2 , 19 , 20 , 23 ]. In particular, the higher the level of emotional and informational support, the higher the confidence and competence in personal health management [ 23 , 42 , 55 ].…”
Section: Discussionmentioning
confidence: 87%
“…In this respect, participating more in social activities in districts with high social trust leads to frequent stimulation of the brain, which may delay the incidence of dementia. Third, low levels of social trust may increase social stress and anxiety, which may result in the stimulation of the hypothalamic-pituitary-adrenal axis (HPA axis) ( 15 ). The stimulation of the HPA axis leads to high blood cortisol levels, which can cause detrimental diseases such as dementia ( 30 , 31 ).…”
Section: Discussionmentioning
confidence: 99%
“…There are other studies from the Republic of Korea which also investigated the association between community-level social trust and various health outcomes such as metabolic syndrome (MetS), cardiovascular disease (CVD), and mortality. In those studies, higher community-level social trust was associated with better health status (13)(14)(15). Meanwhile, there is limited research regarding the association of community-level social trust with the risk of dementia in the Republic of Korea.…”
Section: Introductionmentioning
confidence: 98%
“…According to a recent study, social trust was associated with metabolic syndrome [ 23 ]. It suggests that low social trust may affect high incidence of metabolic syndrome, and metabolic syndrome increase the risk of CVD.…”
Section: Discussionmentioning
confidence: 99%